It Is Hot in the Sun: Antarctic Mosses Have High Temperature Optima for Photosynthesis Despite Cold Climate - Perera-Castro, Alicia V.; Waterman, Melinda J.; Turnbull, Johanna D.; Ashcroft, Michael B.; McKinley, Ella; Watling, Jennifer R.; Bramley-Alves, Jessica; Casanova-Katny, Angelica; Zuniga, Gustavo; Flexas, Jaume; Robinson, Sharon A. (Frontiers in Plant Science, 2020)
The terrestrial flora of Antarctica’s frozen continent is restricted to sparse ice-free areas and dominated by lichens and bryophytes. These plants frequently battle sub-zero temperatures, extreme winds and reduced water availability; all influencing their ability to survive and grow. Antarctic mosses, however, can have canopy temperatures well above air temperature. At midday, canopy temperatures can exceed 15°C, depending on moss turf water content. In this study, the optimum temperature of photosynthesis was determined for six Antarctic moss species: Bryum pseudotriquetrum, Ceratodon purpureus, Chorisodontium aciphyllum, Polytrichastrum alpinum, Sanionia uncinata and Schistidium antarctici collected from King George Island (maritime Antarctica) and/or the Windmill Islands, East Antarctica. Both chlorophyll fluorescence and gas exchange showed maximum values of electron transport rate occurred at canopy temperatures higher than 20°C. The optimum temperature for both net assimilation of CO2 and photoprotective heat dissipation of three East Antarctic species was 20-30°C and at temperatures below 10°C, mesophyll conductance did not significantly differ from 0. Maximum mitochondrial respiration rates occurred at temperatures higher than 35°C and were lower by around 80% at 5°C. Despite the extreme cold conditions that Antarctic mosses face over winter, the photosynthetic apparatus appears optimised to warm temperatures. Our estimation of the total carbon balance suggests that survival in this cold environment may rely on a capacity to maximize photosynthesis for brief periods during summer and minimize respiratory carbon losses in cold conditions.